Investigation of antiviral resistance and escape mutations in children with naive chronic hepatitis B patients and their parents - Tokgöz, Yavuz; Terlemez, Semiha; Sayan, Murat; Kırdar, Sevin (The Turkish Journal of Pediatrics, 2018)
In this study, it was aimed to scan the resistance to nucleoside analogs in naive pediatric patients with chronic hepatitis B treatment and their parents and the rate of accompanying possible escape mutations. A total of 34 children who did not receive any treatment regarding chronic hepatitis B and 19 parents who caused vertical transmission or acquired transmission from father were involved in the study. Serological tests concerning hepatitis B virus and transaminases in conjunction with viral load were studied. HBV genotypes, subgenotypes were determined by surface gene sequencings. The gene mutations coding polymerase (pol) for resistance against nucleoside analogs and escape mutations in the genes coding surface (S) proteins were analyzed with PCR method. All cases were genotype D. Only one pediatric patient was D2; the rest of all pediatric patients and their parents were genotype D1. Resistance was not identified against nucleoside analogs in any children or their parents. HBsAg escape mutations determined in the chronic hepatitis B patients were 18.8% (10 case). It can be speculated with this results that the resistance may not be considered as a problem in the preference of nucleoside analogs in treatment of naive children. Nevertheless, escape mutations were seen as high in both children and parents as well. Since it interests public health on a large scale, advanced studies and evaluation of vaccination escape mutations` rate in broad case series and their follow up are of great importance in the determination of health policies with regard to hepatitis B infection control.
Keywords: antiviral resistance; children; chronic hepatitis B; escape mutations